De Nederlandse economie tijdens de Tweede Wereldoorlog bekeken vanuit een Vlaams/Belgisch perspectief - Buyst, E.; Lefebvre, W.
H.A.M. Klemann, Nederland 1938-1948. Economie en samenleving in jaren van oorlog en bezettingThe Netherlands economy during World War II viewed from a Flemish/Belgian perspectiveHein Klemann’s book provides a general overview of the performance of the Dutch economy during World War II. It also deals with exploitation by the German war machine, production for the black market, price controls, and monetary and fiscal policies. The reconstructed macro-economic data, such as the evolution of real wages, is sometimes prone to serious methodological flaws. For other variables, such as agricultural production in 1945 and international trade, it is clear that more research is necessary to produce reliable indicators. Despite these critical remarks, Klemann’s book offers a valuable synthesis, and other countries, such as Belgium, can use it as a source of inspiration.